EFFECT FRAUD DIAMOND THEORY DETECTING FINANCIAL STATEMENT FRAUD WITH PANDEMIC AS CONTROL VARIABLE (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
The COVID-19 pandemic has caused nationwide economic losses. This condition forces companies to try keeping financial performance stable. What needs to be watched out for during this pandemic is hiding or manipulating company financial statements to improve investors’ interest in investing on the company during this pandemic. Before the pandemic, financial statement fraud cases had often occurred in Indonesia, such as cases of auditor failure, companies revising financial statements, or manipulating false claims to get rewards. This study aims to determine the relationship between financial stability, external pressure, financial targets, ineffective monitoring, change of auditors, and change of directors on financial statement fraud. The sample of this research is pharmaceutical companies listed on the Indonesia Stock Exchange for the period of 2018–2021.This study uses secondary data sources originating from the company’s financial statements. The results of the study stated that financial stability, financial target, change of auditor, and change of director had no effect onfinancial statement fraud. External pressure has a positive effect on financial statement fraud, while ineffective monitoring has a negative effect on financial statement fraud. Keywords: financial statement fraud, pandemic, fraud diamond, pharmacy.